(untitled) (SCIENCE TIME JOURNAL, 2026)
The present study investigates the linguistic characteristics of children’s spontaneous speech in English and Uzbek. Spontaneous speech represents natural and unplanned language production that reflects a child’s cognitive and linguistic development. The research focuses on phonological, lexical, grammatical, and pragmatic features observed in children’s everyday communication. By comparing speech samples from English-speaking and Uzbek-speaking children, the study identifies both universal patterns of language acquisition and language-specific characteristics. The findings demonstrate that while children in both language communities follow similar developmental stages, structural differences between English and Uzbek significantly influence speech production. The results contribute to the fields of psycholinguistics, comparative linguistics, and language acquisition studies.